2004
DOI: 10.4049/jimmunol.173.3.1902
|View full text |Cite
|
Sign up to set email alerts
|

LacdiNAc-Glycans Constitute a Parasite Pattern for Galectin-3-Mediated Immune Recognition

Abstract: Although Galβ1–4GlcNAc (LacNAc) moieties are the most common constituents of N-linked glycans on vertebrate proteins, GalNAcβ1–4GlcNAc (LacdiNAc, LDN)-containing glycans are widespread in invertebrates, such as helminths. We postulated that LDN might be a molecular pattern for recognition of helminth parasites by the immune system. Using LDN-based affinity chromatography and mass spectrometry, we have identified galectin-3 as the major LDN-binding protein in macrophages. By contrast, LDN binding was not observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 41 publications
3
119
0
3
Order By: Relevance
“…Among these, the galectin CGL2 from inky cap mushroom Coprinus cinereus displays in vitro specificity for blood group A oligosaccharides (39,40), whereas the mammalian galectins 2-4 and 8 can recognize A and B oligosaccharides in a concentration-dependent manner (36,37). Although not specific for A oligosaccharides, some galectins can recognize nonreducing terminal GalNAc moieties in exogenous ligands, such as the human galectin-3 that binds to soluble and egg shell-associated glycans of the parasite helminth Schistosoma mansoni displaying GalNAc␤1-4GlcNAc (41). Furthermore, recent studies have shown that in vivo CGL2 actually binds the "galactosylated core fucose" glycotope (42), whereas CGL3, another galectin from C. cinereus, recognizes N-acetylhexosamines (HexNAc) such as in GlcNAc-GlcNAc or GalNAc-GlcNAc in vitro but not lactose (43).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the galectin CGL2 from inky cap mushroom Coprinus cinereus displays in vitro specificity for blood group A oligosaccharides (39,40), whereas the mammalian galectins 2-4 and 8 can recognize A and B oligosaccharides in a concentration-dependent manner (36,37). Although not specific for A oligosaccharides, some galectins can recognize nonreducing terminal GalNAc moieties in exogenous ligands, such as the human galectin-3 that binds to soluble and egg shell-associated glycans of the parasite helminth Schistosoma mansoni displaying GalNAc␤1-4GlcNAc (41). Furthermore, recent studies have shown that in vivo CGL2 actually binds the "galactosylated core fucose" glycotope (42), whereas CGL3, another galectin from C. cinereus, recognizes N-acetylhexosamines (HexNAc) such as in GlcNAc-GlcNAc or GalNAc-GlcNAc in vitro but not lactose (43).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of its ability to recognize glycans containing b-galactoside, galectin-3 binds to glycoconjugates synthesized by several pathogens such as Mycobacterium tuberculosis [16], Leishmania major [17], Trypanosoma cruzi [18], Schistosoma mansoni [19] and Candida albicans [20]. Recently, galectin-3 and TLR2 have been found to be associated in C. albicans-infected differentiated macrophages, an association that has been considered essential for TLR2-dependent cytokine production in response to the fungal infection [21].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular galectin-3 is able to activate cells [4][5][6][7][8][9] cell-cell and cell-extracellular matrix interactions [10][11][12], and induce phagocyte migration [13]. However, galectin-3 also functions inside the cells and can contribute to macrophage functions that are essential in the cellular response during the infectious process, such as cell survival [14] and phagocytosis [15].As a result of its ability to recognize glycans containing b-galactoside, galectin-3 binds to glycoconjugates synthesized by several pathogens such as Mycobacterium tuberculosis [16], Leishmania major [17], Trypanosoma cruzi [18], Schistosoma mansoni [19] and Candida albicans [20]. Recently, galectin-3 and TLR2 have been found to be associated in C. albicans-infected differentiated macrophages, an association that has been considered essential for TLR2-dependent cytokine production in response to the fungal infection [21].…”
mentioning
confidence: 99%
“…It has been suggested that galectin-3 may serve as a pathogen pattern recognition receptor to visualize PAMPs from bacteria (19,20), parasites (21,22), and fungi (23,24). Moreover, it has been reported that galectin-3 interacts with LPS via both NЈ and CЈ terminals (25).…”
mentioning
confidence: 99%